2018
DOI: 10.1016/j.geothermics.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding amorphous silica scaling under well-constrained conditions inside geothermal pipelines

Abstract: Amorphous silica is a common precipitate in modern and ancient hot springs and in geothermal power plants, yet the corresponding precipitation rates and mechanisms are still highly debated, primarily due to the plethora of parameters that can affect the reactions in natural waters. Here, we report the results from a first ever industrial-scale time-resolved (1 day to 10 weeks) study of silica precipitation conducted at the Hellisheiði geothermal power plant (SW-Iceland). We show that such in-work pipelines of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 51 publications
(84 reference statements)
1
26
0
Order By: Relevance
“…It is well documented that silica NPs synthesized from monosilicic acid are internally highly disordered and hydrated at their surfaces [31]. Previous studies found that the initially formed NPs if aggregated continued their growth, resulting in some cases in larger homogeneous silica spheres [31,5859], and this may explain why silica is such a persistent scaling material in hydrothermal systems.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that silica NPs synthesized from monosilicic acid are internally highly disordered and hydrated at their surfaces [31]. Previous studies found that the initially formed NPs if aggregated continued their growth, resulting in some cases in larger homogeneous silica spheres [31,5859], and this may explain why silica is such a persistent scaling material in hydrothermal systems.…”
Section: Resultsmentioning
confidence: 99%
“…All the parameters previously shown which influences these processes, have been optimized in both reactors. In particular, to maximise the probability of deposits, the scaling reactor has been designed with: (1) a suitable geometry in order to increase contact area between flow particles and surfaces; (2) an appropriate mechanism for promoting turbulence and the number of impacts between particles and surfaces, according with the equations developed in [4]; (3) pH values equal to 8.5, (4) silica seeds addition. To control the flow pH and salinity, additional substances are mixed with the geothermal fluid after the heat exchanger.…”
Section: Fig 8 Retention System Designmentioning
confidence: 99%
“…Two main kind of processes have the tendency to take place: (1) molecular deposition of monomeric silica directly onto solid surfaces and (2) polymerization of monomeric silica to form silica polymers with homogeneous nucleation and growth of suspended particles. The presence of these two dominant and essentially competing pathways, is shown in Fig.1 and it has been extensively studied and reported by many authors [1], [3] [4]. The predominance of one process over the other depends on many factors such as water environment, pH-value, ionic strength, temperature, flow velocity, salinity and degree of supersaturation with respect to amorphous silica which is defined as the ratio between silica concentration and equilibrium solubility at the given condition [1].…”
Section: Introduction and Soamentioning
confidence: 99%
“…The synthesis of sodium silicate from different silica (SiO2) sources such as clay [14] and coal fly ash [15] has been reported in literature. Another highly potential source is geothermal sludge that contains a high amount of silica [16][17][18][19]. The existence of numerous volcanoes in Indonesia has made the country rich in geothermal sources for the production of electrical power.…”
Section: Introductionmentioning
confidence: 99%
“…Geo Dipa Energi at Dieng, which produces 60 MW electricity. Despite the high potency of geothermal resource to generate electricity, it is frequently found that the geothermal fluid brings up a high amount of silica-containing brine from the earth that can precipitate and causes massive scaling problems in the pipelines [16][17][18][19]. Controlled precipitation, extraction, and utilization of silica from geothermal sludge is therefore an attractive solution in order to eliminate and, at the same time, increase the value of "wastes" resulted from the geothermal power plant.…”
Section: Introductionmentioning
confidence: 99%